Protective Effects of Quercetin-Loaded Pumpkin Seed Oil Nano-Emulsion on Testosterone-Induced Benign Prostatic Hyperplasia in Rats: Quercetin Nano-Emulsion Mitigates Testosterone-Induced Prostatic Hyperplasia - Shirmohammadi Yazdi, Mohammad; Heidari, Reza; Panahi, Negar; Chamanara, Mohsen; Nourmohammadi, Abbas (Iranian Journal of Pharmaceutical Sciences, 2025)
Oxidative stress and inflammation play a significant role in the development of testosterone-induced benign prostatic hyperplasia (BPH) and prostate cancer. Quercetin, a polyphenolic compound with antioxidant and anti-inflammatory properties, has limited gastrointestinal absorption. Pumpkin seed oil, rich in β-sitosterol, provides anti-inflammatory and antioxidant benefits. This study evaluated the protective effects of a quercetin-loaded pumpkin seed oil nano-emulsion on BPH in rats. Thirty-six adult male Wistar rats were divided into six groups (n=6 each): control, healthy, quercetin-loaded pumpkin seed oil nano-emulsion, pumpkin seed oil nano-emulsion, quercetin, and finasteride. Except for the healthy group, all groups received intramuscular testosterone enanthate (100 mg/mL) for five consecutive days each week over four weeks. Blood and pathological assessments were conducted to evaluate the effects of the treatments. Statistical analyses were performed using One-Way ANOVA, Paired T-Test, Kruskal-Wallis, and IBM SPSS version 25, with a significance level of p < 0.05. Significant improvements in inflammatory and antioxidant markers were observed in the quercetin-loaded pumpkin seed oil nano-emulsion group and the finasteride group compared to the quercetin, pumpkin seed oil nano-emulsion, and control groups (P<0.05). Hyperplastic and hypertrophic lesions were markedly reduced in the quercetin-loaded pumpkin seed oil nano-emulsion group compared to the control group, demonstrating superior efficacy relative to finasteride (P<0.05). The quercetin-loaded pumpkin seed oil nano-emulsion showed better outcomes in treating or preventing BPH than finasteride, with fewer side effects. This nano-emulsion could be a promising alternative or adjunct therapy for individuals at risk of BPH, such as athletes and the elderly.